Neural networks in optimization of the software development process - Honchar, Y. A. (ХНУРЕ, 2019)
Software and hardware increasingly take a part of our life in the information era. Projects are filling with functionality, are becoming more significant and difficult to manage. The development time and the number of errors continuously increases. The development process includes steps as following: requirements analysis, design, implementation, testing, documentation, and support. They require significant effort that needs to be appropriately shared among all workers. But neural networks can help optimize every step of tedious software development.